Response of cardiorespiratory system during maximal exercise cycle ergometer test in women cross-country skiers with different skills levels - I. O. Garnov; T. P. Loginova; E. R. Boyko (National Electronic Information Consortium (NEICON), 2023)
Objective: to estimate the functional features of the cardiorespiratory system of female cross-country skiers with different skills levels at the maximal bicycle ergometer test.Material and methods: 70 female cross-country skiers were divided into three groups. The first group included 21 cross-country skiers with first adult sporting rank, the second - 25 candidates in master of sports, the third group - 24 sport masters in cross-country skiing. Maximal exercise tests were used to determine cardiorespiratory fitness via spiroergometric system «Oxycon Pro» (Jaeger, Hoechberg, Germany).Results: The most notable differences were observed between the first-class and the masters of the sports groups. In the first-class group the heart rate during the maximal exercise test was, on average, 11 beats/min higher than in the master of sports group (p<0.05), and the oxygen consumption at the anaerobic threshold was, on average, lower by 7.7 ml/min/kg (p < 0.05) when comparing the same groups.Conclusion: The influence of skills levels on physiological parameters at maximal bicycle ergometer test was shown. The capacity in the first group occurs due to cardiovascular system tension, and the same in the group high qualification skiers happen due to the mechanisms of oxygen transport development.